Some Tactical Problems in Digital Simulation - Conway, R. W. (Management Science, 1963)
This paper is concerned with the manner in which an investigation by simulated experimentation is conducted, after the model has been formulated and the computer program completed. It considers the problem of estimating the precision of the results obtained, and methods of improving the precision of results. Alternative procedures are discussed and recommendations are given.